AB0220 What Proportion of Patients Fail To Achieve CDAI and SDAI Remission Based on Physician Global Assessment? An Analysis from A Prospective, Observational Registry. (15th July 2016) - Starr, M.; Haraoui, B.; Choquette, D.; Bessette, L.; Chow, A.; Baer, P.; Kapur, S.; Kelsall, J.T.; Teo, M.; Rampakakis, E.; Psaradellis, E.; Nantel, F.; et al.
Abstract : Background: Physician's Global Assessment of Disease Activity (MDGA) is a measure that is frequently incorporated in disease activity indices which reflects the physician's perception of disease activity in rheumatoid arthritis (RA). Objectives: The aim of this analysis was to assess the proportion of patients failing to achieve CDAI and SDAI remission based on MDGA in a real-world, routine clinical care setting in Canada. Methods: BioTRAC is an ongoing, prospective registry of patients initiating treatment for RA, ankylosing spondylitis (AS), or psoriatic arthritis (PsA) with infliximab (IFX) or golimumab (GLM). Eligible patients for this analysis included RA patients treated with IFX or GLM between 2005 and 2015. Modified versions of CDAI (mCDAI) and SDAI (mSDAI) were calculated by omitting MDGA from the formulas. Correlation of the standard and modified versions of each index was assessed with the Pearson's correlation coefficient. ROC curve analysis was used to identify new thresholds for the modified versions of low disease activity (LDA) and remission. Cross-tabulations with the Chi-square test were used to assess the agreement between the standard and modified definitions of remission and LDA. Results: A total of 1206 patients were included in the analysis with a mean (SD) age of 56.1 (13.4) years and a disease duration of 8.4 (8.9) years. A strong positive correlation was observed between the standard and modified versions of CDAI (r=0.99; P<0.001) and SDAI (r=0.99; P<0.001). Based on ROC analysis the new thresholds for remission and LDA were: CDAI (remission=2.65, LDA=10.05) and SDAI (remission=3.31, LDA=10.73). The proportion of patients achieving remission by both indices was 17.8% and 19.5%, patients not achieving remission by both indices was 75.3% and 74.4%, and patients achieving remission by the new thresholds only was 6.9% and 6.1%, for CDAI and SDAI, respectively. Cross-tabulation of the standard and modified thresholds showed that an additional 8.4% and 7.6% of non-remission cases for CDAI and SDAI, respectively, would be classified as remission with the modified definitions. Similarly, an additional 17.6% and 15.1% of non-LDA cases for CDAI and SDAI, respectively, would be classified as LDA. Conclusions: The results of this analysis showed that MDGA could account for up to 8% of non-remission cases and up to 18% of non-LDA cases as measured by CDAI and SDAI. Omission of MDGA from these disease activity indices could have a significant impact on patient management in preventing overtreatment with DMARDs and biologics and avoiding unnecessary switching of DMARDs and biologics. Disclosure of Interest: M. Starr: None declared, B. Haraoui: None declared, D. Choquette: None declared, L. Bessette: None declared, A. Chow: None declared, P. Baer: None declared, S. Kapur: None declared, J. Kelsall: None declared, M. Teo: None declared, E. Rampakakis Employee of: JSS, E. Psaradellis Employee of: JSS, F. Nantel Employee of: Janssen, A. Lehman Employee of: Janssen, B. Osborne Employee of: Janssen, K. Maslova Employee of: Janssen, C. Tkaczyk Employee of: Janssen